Empirical Analysis for Stock Price Prediction Using NARX Model with Exogenous Technical Indicators - Ali H. Dhafer; Gamal Alkawsi; Abdulaleem Z. Al-Othmani; Huda M. Alshanbari; Yahia Baashar; Fauzias Mat Nor; Nuradli Ridzwan Shah Mohd Dali; Khairil Faizal Khairi (Hindawi, 2024)
Indexed by WOS/Scopus/ERA